Co-activation of GR and PPARγ in murine skin prevents worsening of atopic march - Deckers, Julie (J Invest Dermatol, 2018)
Children with atopic dermatitis (AD) show an increased risk to develop asthma later in life, a phenomenon referred to as ‘atopic march’, which emphasizes the need for secondary prevention therapies. This study aimed to investigate whether relief of skin inflammation by glucocorticoids and PPARγ-agonists might influence the subsequent development of asthma in a murine model for the atopic march in which mice were repeatedly exposed to house dust mite (HDM) via the skin, followed by exposure to HDM in lungs. To abrogate AD, mice received topical treatment with GR/PPARγ-agonists. Nuclear receptor ligand effects were assessed on primary keratinocytes and dendritic cells, as central players in skin inflammation. Prior HDM-induced skin inflammation aggravates allergic airway inflammation and induces a mixed Th2/Th17 response in the lungs. Cutaneous combined activation of GR/PPARγ reduced skin inflammation to a higher extent compared to single activation. Additive anti-inflammatory effects were more prominent in dendritic cells, as compared to keratinocytes. Alleviation of allergic skin inflammation by activation of GR/PPARγ appeared insufficient to avoid the allergic immune response in the lungs but efficiently reduced asthma severity by counteracting the Th17 response. GR/PPARγ co-activation represents a potent remedy against allergic skin inflammation and worsening of the atopic march.